Design of Moringa Leaf Dryer Based on Programmable Logic Control Laboratory Scale - Yudha, Fitroh Anugrah Kusuma; Fadullah, Ikhsan Fakhri; Kurniawan, Aditya; Ardiyansyah, Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Moringa plants can be found in most tropical and subtropical climates. In some parts of Indonesia, the plant is called kelor or marungga. People need the tree as a source of protein, vitamins, minerals, and carbohydrates. The plant contains more than 90 nutrients, antioxidants, and 8 essential amino acids, called the ‘elixir tree’. The problem with this plant is that its leaves are easily damaged when picked. One way to avoid this is to perform a drying process. This Moringa dryer consists of an inner cabinet made of aluminum and an outer side made of zinc. The cabinet measures 40 cm long, 35 cm wide, and 35 cm high, has three shelves arranged horizontally, and each shelf can dry between 100 grams to 200 grams of moringa leaves simultaneously. In addition, it has a heater consisting of two 125-watt heaters and two upper and lower fans. In the first experiment, Moringa leaves were dried for 9 hours at 40°C, yielding 30g of dried leaves from 100g of fresh leaves. The second experiment lasted 6 hours at 50 °C, yielding 30 g of dried leaves from 100 g of fresh leaves. Finally, the leaves were dried for 3 hours at 60°C, yielding 30g of dried leaves from the initial 100g. These results also show a large weight loss at various temperatures and durations. After calculating the percentage of weight loss, it was found that the leaves lost 70% of their weight. Outseal PLC can automatically control the drying process according to the pre-programmed program. Temperature and humidity sensors maintain the nutritional quality and texture of the moringa leaves produced by controlling the dryer environment appropriately. This tool can be used easily by users without requiring high technical skills.